Onikomikosis Kandida yang Diterapi dengan Itrakonazol Dosis Denyut - Mamuaja, Enricco H.; Susanti, Ratna I.; Suling, Pieter L.; Kapantow, Grace M. (Jurnal Biomedik : JBM, 2017)
Abstract: Candidiasis onychomycosis is a nail disorder caused by candida spp. as the most common cause in Indonesia. The first line therapy for this case is pulse dosing of itraconazole (2x200 mg/day for 7 days with 3-week interval); 2 pulse doses for finger nails and 3-4 pulse doses for toe nails. We reported a male of 60 years old with nail destruction and thickening of the thumb and ring finger of the right hand since six months ago. In the beginning, the nails appeared dull and then became yellowish, thickened, and brittled. Dermatology examination of the 1st and 4th finger of the right hand showed onycholysis, onychodistrophy, subungual hyperkeratosis, and yellowish discoloration. KOH 20% test found no long hypha with septa. Moreover, Gram staining showed no spora, budding cell, or pseudohypha. Repeated ten-day culture resulted in Candida parapsilosis. The treatment was succeded with two doses of itraconazole 2x200 mg for 7 days, with interval of 3 weeks. In this case, candidiasis onychomycosis was invasive in nails with onycholysis which looked like distal subungual onychomycosis. The growth of candida colony was fully spread in the Petri disk in 10 days, therefore, dermatophyte infection could not be excluded. Conclusion: Pulse therapy with two-dose itraconazole succedeed in the treatment of candidiasis onychomycosis of the finger nails.Kata kunci: candidiasis onychomycosis, Candida parapsilosis, itraconazole pulse therapyAbstrak: Onikomikosis kandida adalah kelainan kuku akibat infeksi candida spp. yang merupakan penyebab terbanyak di Indonesia. Penatalaksanaan utama ialah itrakonazol dosis denyut (2x200 mg/hari selama 7 hari, istirahat 3 minggu) sebanyak 2 denyut untuk kuku tangan dan 3-4 denyut untuk kuku kaki. Kami melaporkan kasus seorang laki-laki 60 tahun dengan kerusakan dan penebalan kuku ibu jari dan jari manis tangan kanan sejak sekitar 6 bulan. Awalnya kuku berwarna putih suram kemudian berubah menjadi kekuningan, menebal dan rusak. Status dermatologikus memperlihatkan kuku jari I dan jari IV tangan kanan terdapat onikolisis, onikodistrofi, hiperkeratosis subungual, dan diskolorasi kekuningan. Pada pemeriksaan KOH 20% tidak ditemukan hifa panjang bersepta; pemeriksaan Gram tidak ditemukan spora, budding cell, dan pseudohifa. Hasil biakan berulang selama 10 hari ditemukan Candida parapsilosis. Terapi berhasil dengan pemberian itrakonazol 2x200 mg selama 7 hari, istirahat 3 minggu, sebanyak 2 denyut. Onikomikosis kandida pada kasus ini tergolong invasif pada kuku yang sudah onikolisis, menyerupai onikomikosis subungual distal. Pertumbuhan koloni kandida yang cepat memenuhi cawan menyebabkan lamanya kultur hanya 10 hari sehingga kemungkinan adanya infeksi dermatofita belum dapat disingkirkan. Simpulan: Terapi itrakonazol sebanyak 2 dosis denyut memperlihatkan keberhasilan pada onikomikosis candida di jari tangan.Kata kunci: onikomikosis kandida, Candida parapsilosis, itrakonazol dosis denyut